THE USE OF ORAL PEER FEEDBACK TO MINIMIZE THE STUDENTS’ ERRORS IN PRONOUNCING ENGLISH CONSONANT SOUNDS /p/, /f/ and /v/ IN READING ALOUD - Kinanty Kintamani; Asep Dudi Kurnia; Didih Faridah (JALL (Journal of Applied Linguistics and Literacy), 2019)
ABSTRACT  This study reports on the use of oral peer feedback to minimize the students’ errors in pronouncing English consonant sounds /p/, /f/ and /v/. It was a  case at the twelfth grade in one of senior high schools in Tasikmalaya. Furthermore, this study was aimed to find out the extent to which the students make errors in pronouncing English consonant sounds /p/, /f/ and /v/, how the teacher minimizes the students’ errors in pronouncing English consonant sounds /p/, /f/ and /v/ by means of oral peer feedback and the teacher’s reasons of using oral peer feedback to minimize the errors in pronouncing English consonant sounds /p/, /f/ and /v/. Furthermore, in conducting this study the writer used qualitative research in which case study. To collect the data from participants in this research, there was six students at the twelfth grade and an English teacher who taught English pronunciation in reading activities. Classroom observation and interview were the instruments used by the writer in collecting the data. Based on the research findings, the writer concluded three major conclusions. First, the writer concluded that the majority of the students were able to pronounce the English consonant sounds /p/, /f/ and /v/ correctly that have been proven by the results of students’ pronunciation. Second, the teacher taught the students about reading comprehension that contained the sounds of /p/, /f/ and /v/ with the use of oral peer feedback. In short, it could be seen that teacher’s ways in minimizing students’ errors in pronouncing English consonant sounds /p/, /f/ and /v/ by means of oral peer feedback was succesfully completed by the teacher through the activities in classroom observation. In addition, teacher's ways in implementing oral peer feedback was relevant with the theory from Brookhart (2008, p. 70) about the procedure in implementing oral peer feedback. Finally, teacher’s reasons of using oral peer feedback to minimize the errors in pronouncing English consonant sounds /p/, /f/ and /v/. The writer concluded that the teacher has the main reason for choosing oral peer feedback as one of the ways to minimize students’ error in pronouncing /p/, /f/ and /v/. The teacher argued that the use of oral peer feedback was one of the ways for minimizing students’ errors because the students were demanded to give corrections toward students' errors in pronouncing the words. The students were more felt comfort when they assessed by their friends. Therefore, they will enhance their skill by the corrections given by the other students in oral peer feedback. Moreover, the writer suggests that the further researchers to investigate the cause of students’ error of EFL learner specifically. Key words :oral peer feedback, students’ error, English consonant sounds.